MOBILE HUMAN POWERED RAKING EQUIPMENT (MHPRE) FOR SPREADING AND MIXING PADDY IN SUN DRYING - Galindo, Ronald M (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
The drying of paddy after harvest is commonly done on concrete pavement by spreading and mixing using the traditional manual raking tool to prepare it prior to storing and milling. During the drying process, when paddy is not uniformly mixed at the desired layer depth, grain quality is reduced especially if drying is delayed, incomplete or ineffective. For these reasons, a Mobile Human Powered Raking Equipment (MHPRE) was developed to uniformly spread and mix the paddy for sun drying in a shorter time. The study was carried out through the development of a two-wheeled detachable and mountable paddy rake type spreader and mixer using a Polypropylene Random Copolymer (PPR) pipe, the development of a four-wheeled human powered vehicle that pulls the paddy rake spreader and mixer and the evaluation of the performance of the MHPRE compared to the traditional manual paddy spreading and mixing. The two-wheeled innovative detachable and mountable PPR raking tool with adjustable paddy leveling plate was found to be effective in spreading and mixing paddy uniformly at the desired layer depth of 4 cm with respect to time, cost and quality. The MHPRE was found to be stable, durable, safe to operate and effective in spreading and mixing uniformly on concrete drying pavement with a lesser period of time. Furthermore, savings of 52.38% was attained in an 8-hour sun drying of paddy using the MHPRE compared to the traditional manual paddy spreading and mixing on concrete pavement. Results suggest that the MHPRE is now ready for deployment in the agricultural community in the country.